(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article describes the history of the origin of the markets, their functional functions in the Middle Ages and today, the work carried out at the Alloqulikhan team and caravanserai at the beginning of the 20th century, and its impact on cultural heritage.